Measuring tourist satisfaction: A factor-cluster segmentation approach - Agiomirgianakis, George; Mihiotis, Athanasios; Andriotis, Konstantinos (My University, 2008)
Tourist satisfaction has been considered as a tool for increasing destination competitiveness. In an attempt to gain a better understanding of tourists' satisfaction in an island mass destination this study has taken Crete as a case with the aim to identify the underlying dimensions of tourists' satisfaction, to investigate whether tourists could be grouped into distinct segments and to examine the differences between the segments and their sociodemographic and travel arrangement characteristics. A segmentation procedure based on destination dimensions produced three clusters: the `Higher-Satisfied'; the `In-Betweeners'; and the `Lower-Satisfied'. The implications and the conclusions of the study are provided in relation to the marketing of the island of Crete.
Keywords: Cluster; Factor analysis; Satisfaction; Segmentation; Sociodemographic characteristics; Crete